Analysis of the Level of Road Damage Due to Vehicle Volume on Rigid Perkerasa on the Pantura Tegal - Pemalang Road in Tegal Regency - Wahidin, Wahidin (Universitas Malikussaleh, 2019)
Traffic volume is one of the factors causing road damage. Rigid pavement is generally used on roads that have fairly heavy traffic. With the increasing number of vehicles it is possible that the road will suffer damage in a relatively short time .The purpose of this study was to determine the effect of the volume of vehicle types with the level of road damage and the relationship of the volume of vehicle types with the level of road damage on rigid pavement. So it can be predicted in advance the value of road damage that will occur. The method used in this research is the method of analyzing vehicle volume and the level of road damage using the regression method. Namely to get the function of the relationship with the value of R ² (coefficient of determination) which shows the magnitude of the effect of changes in the variation of the volume of vehicle types to changes in the value of road damage. This research was conducted in the Pantura Tegal - Pemalang Lane section . There is a relationship between the volume of vehicle types and the value of road damage. With the result R² = 0, 892 show k of damage roads that influenced the volume type of light vehicles and heavy vehicles have a percentage of 8 9.2 %. With the results of the heavy vehicle equation (X2) and the value of road damage (Y) that is Y = 0, 27 X2 + 8 , 887 . From this equation can be described as follows .. Regression coefficient X2 ( a ) = 0 , 27 , meaning that heavy vehicles by 100 vehicles / day will increase the level of road damage by 27 , constant (c) = If no vehicles pass a road , the road will suffer a road damage of 8 , 887.